2022
DOI: 10.21037/jgo-22-861
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient is a good marker in predicting the prognosis in colorectal cancer liver metastases: a diagnostic study

Abstract: Background: Colorectal cancer (CRC) is one of the most common malignant tumors. Up to 10% CRC patients can have liver metastases at the first diagnosis. At present, clinical diagnosis of CRC liver metastasis (CRCLM) is mostly based on imaging, and there is a certain false-positive rate and false-negative rate.Improving the diagnostic accuracy of imaging for CRCLM is highly significant. Apparent diffusion coefficients showed high predicting value in other cancers. The aim of the present study was to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Therefore, patients with low ADC are relatively prone to metastasis, leading to poor prognosis of patients. This had been confirmed in patients with CRC and other malignant tumors ( 18 , 25 - 27 ), supporting this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, patients with low ADC are relatively prone to metastasis, leading to poor prognosis of patients. This had been confirmed in patients with CRC and other malignant tumors ( 18 , 25 - 27 ), supporting this study.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the high cell density in solid malignant tumor tissue, the ADC in malignant tumor tissue is often in a reduced state. At present, the ADC is used to predict the prognosis of patients with malignant tumor ( 19 - 21 ), and has also been reported in patients with CRC ( 18 ). In the field of neoadjuvant chemotherapy, studies have also confirmed that the ADC is significantly related to the efficacy of neoadjuvant chemotherapy in patients with breast cancer and osteosarcoma ( 16 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation